Performance comparison of cooling systems using R410a and RE170 as working fluids at various condensing temperature - Setyawan Andriyanto; Mitrakusuma Windy H.; Simbolon Luga M. (BIO Web of Conferences)
In addition to being used as a fuel and propellant, dimethyl ether (RE170) can also be used as an environmentally friendly refrigerant. Apart from having zero ozone depletion potential (ODP), this compound also has a very low global warming potential (GWP), making it safe for the environment. This study aims to compare the performance of refrigeration machines using RE170 and R410, which has long been used as a refrigerant in air conditioning systems. The study was conducted at various evaporation and condensation temperatures. The results showed that RE170 does have a lower cooling capacity, about 41.5% of the cooling capacity of R410A. However, the power required on the system with RE170 is very low, which is only about 35.5% compared to the power required by the system with R410. As a result, the system with RE170 has 16.9% better energy efficiency. Thus, RE170 is not only environmentally friendly but also energy efficient. Another important finding of this study is that RE170 is superior to R410A in terms of energy efficiency at high condensing temperature.